2020
DOI: 10.25259/sni_280_2020
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma in the sphenoid sinus: A case report and review of literature

Abstract: Background: Non-Hodgkin lymphomas (NHLs) in paranasal sinus are uncommon, accounting for 0.17–2% of all NHL cases; it is especially rare in the sphenoid sinus. In this report, we describe a case of NHL in the sphenoid sinus. Case Description: A 66-year-old man presented with a sudden left eye movement disorder. His head computed tomography and gadolinium-enhanced magnetic resonance imaging (Gd-MRI) showed a mass lesion extending around the left sphenoid sinus. However, the tumor regrowth about twice was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They also reviewed 17 cases of nasopharyngeal B-cell lymphoma, but none of the cases of nasopharyngeal B-cell lymphoma presented cranial nerve palsies nor hypopituitarism [ 3 ]. Similarly, Wajima et al reviewed 15 cases of sphenoidal lymphoma [ 5 ]; 73.3% patients initially presented with ptosis or diplopia caused by II, III, IV, or VI palsy, but not hypopituitarism. Furthermore, they reported that the most commonly extended area of tumor was the cavernous sinus (33.3%) as shown in our case [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reviewed 17 cases of nasopharyngeal B-cell lymphoma, but none of the cases of nasopharyngeal B-cell lymphoma presented cranial nerve palsies nor hypopituitarism [ 3 ]. Similarly, Wajima et al reviewed 15 cases of sphenoidal lymphoma [ 5 ]; 73.3% patients initially presented with ptosis or diplopia caused by II, III, IV, or VI palsy, but not hypopituitarism. Furthermore, they reported that the most commonly extended area of tumor was the cavernous sinus (33.3%) as shown in our case [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wajima et al reviewed 15 cases of sphenoidal lymphoma [ 5 ]; 73.3% patients initially presented with ptosis or diplopia caused by II, III, IV, or VI palsy, but not hypopituitarism. Furthermore, they reported that the most commonly extended area of tumor was the cavernous sinus (33.3%) as shown in our case [ 5 ]. Together, it is clinically important to consider that sphenoidal lymphoma could simultaneously cause both hypopituitarism and hemi-cranial nerve palsies.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic symptoms may be present in BCL (especially in cases with systemic involvement), while they are relatively rare in ENKTL 1794 . In a series of head and neck lymphoma patients, only 13% of ENKTL patients were diagnosed with B symptoms at the time of presentation 1795 .…”
Section: Sinonasal Lymphomamentioning
confidence: 99%